Morphological alterations in the dentition of type I diabetes mellitus patients - Andamuthu Yamunadevi; Praveen S Basandi; G S Madhushankari; Mandana Donoghue; Alur Manjunath; Manickam Selvamani; H K Puneeth (Wolters Kluwer Medknow Publications, 2014)
Introduction: Type 1 diabetes mellitus (DM) is an endocrine disorder that occurs commonly in an age group, where the development of primary and permanent dentition takes place. As altered endocrine functions may affect the shape and size of teeth leading to dental anomalies, this study was conducted to look for the occurrence of any dental anomalies in type I DM patients. Materials and Methods: A diabetic camp was conducted at Alur Chandrashekharappa Memorial Hospital, Davangere, where 30 diabetic patients were examined and the impressions of their maxillary and mandibular arches were recorded. Age and sex matched controls were selected randomly, and similar recordings were done. Results: Type I diabetic patients showed statistically significant (P < 0.001) morphological alterations of total number of cusps, including presence of 6 th cusp in mandibular molars and extra cusps in mandibular premolars. Other alterations such as microdontia, flower shaped mandibular molars, prominent cusp of carabelli, and oblique ridge in maxillary molars were also noted. Severe attrition was found in 11 (36.6%) of the diabetic patients, whereas the control group showed attrition only in 2 (6.8%) patients. Conclusion: Remarkable morphological alterations do occur in the dentition of type I DM patients.